Secang Heartwood Ethanolic Extract (Caesalpinia sappan L.) Inhibits Mesenchymal Stem Cells Senescence - Asri Mega Putri; Nindya Budiana Putri; Rahmawaty Rachmady; Idlohatud Dilalah; Retno Murwanti; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2017)
Antioxidants have the ability to scavenge free radicals, leading to inhibition of cells senescence. Secang Heartwood (Caesalpinia sappan L.) contains flavonoid brazilein, known of its high antioxidant activity. However, the activity of secang as senescent cells inhibitor has not been known. The aim of this study is to explore the potential of Caesalpinia sappan ethanolic extract (CSE) as free radical scavenger, thus inhibits senescent cells. Two concentrations of SE under IC50, 2µg/mL, 5µg/mL and 10µg/mL were applied on Mesenchymal Stem Cells (MSCs) and combined with 5µM of doxorubicin (Dox) as senescence inductor; both of them were compared with MSCs-Dox group. X-gal, chromogenic substrate of senescent cells, was given on MSCs, giving blue stain on senescent cells. To explore brazilein mechanism in senescence inhibition, molecular docking using PLANTS on topoisomerase II was performed. MSCs that treated with 10µg/mL of SE qualitatively showed reduction intensity of blue stain. Number of stained cells also reduced from 76% of MSCs-Dox to 38 % of 10µg/mL SE-Dox group. Docking score shows that brazilein (-86.91) is more stable to interact with topoisomerase II than doxorubicin (-82.46) and has same binding site (Val 174). These findings demonstrate starting knowledge on CSE potential as senescent cells inhibitor through brazilein activity on topoisomerase II.Keyword: Caesalpinia sappan L., Senescence, β-galactosidase, Molecular Docking